Barriers and facilitators to birth without epidural in a tertiary obstetric referral center: Perspectives of health care professionals and patients. Issue 3 (18th December 2017) - Knox, Alyssa; Rouleau, Geneviève; Semenic, Sonia; Khongkham, Malisa; Ciofani, Luisa
Abstract: Background: Epidural rates are high in tertiary obstetric referral centers, even though many patients in tertiary settings might not want or need epidural analgesia. Epidural rates are influenced by factors including labor support and routine medical intervention. This study aimed to identify barriers and facilitators to birth without epidural in a Canadian tertiary center, from the perspectives of doctors, nurses, and patients. Methods: In this qualitative exploratory study, individual, semi‐structured interviews were conducted in 2016 with 5 doctors, 5 nurses, and 4 patients who intended to birth without epidural. Interviews were audio‐recorded, transcribed, and analyzed using inductive qualitative thematic analysis. Results: Several contextual factors in the tertiary center facilitated or were barriers to birth without epidural. The following themes emerged: (1) differing perceptions of pain, (2) being ready for things to go wrong, (3) labor support is more labor intensive, and (4) having insufficient resources for birth without epidural. Conclusions: Reconciling patient birth goals with staff focus on patient safety is challenging in the tertiary context. Discrepancies between health care professional and patient attitudes about childbirth pain may influence decision‐making about epidural use. Maintaining labor support skills is challenging for health care professionals who have limited exposure to birth without epidural. There is a need to allocate dedicated resources to better support birth without epidural. Specifically, support could be improved through the implementation of guidelines for assessment and management of labor pain, provision of a variety of pain management options, and labor support training for health care professionals.